FROM FATWA TO COMPLIANCE IN ISLAMIC FINANCIAL ENFORCEMENT: Designing Governance and Supervision Frameworks for Sharia Fintech in Indonesia - Purnama, Noer; Sulistiani, Lies; Muttaqin, Zainal (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2025)
This study examines how DSN-MUI fatwas can be transformed into operational and binding legal norms within the governance of Sharia fintech in Indonesia. The main problem identified is the absence of an integration mechanism between fatwas and OJK regulations, resulting in a dualistic supervisory framework that creates legal uncertainty and weakens the enforcement of Sharia compliance. Using a normative legal research method with legislative, conceptual, and comparative approaches, this study analyzes regulatory gaps, supervisory structures, and governance practices across several countries. The findings indicate that the dual authority model hampers regulatory effectiveness and undermines public trust in Sharia fintech. This study recommends an integrated governance framework through normative harmonization, the establishment of an OJK-DSN-MUI coordination platform, and the incorporation of fatwa provisions into formal regulations to strengthen legal legitimacy, ensure Sharia compliance, and enhance consumer protection. Study analyzes the transformation of fatwas into enforceable legal frameworks within the governance of Sharia fintech in Indonesia. Using a normative and comparative legal approach, this study examines the relationship between the regulations of the Financial Services Authority (OJK) and the fatwas issued by the National Sharia Council–Indonesian Ulema Council (DSN–MUI).